PENGARUH MODEL PEMBELAJARAN KOOPERATIF SCRAMBLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PAI DAN BUDI PEKERTI - Dara Nur Fadilla; Khoirotus Silfiyah; Alaika Abdi Muhammad; Ahmad Shofiyuddin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2024)
Teaching is the main task of an educator. Creative educators will always create ideas for designing new learning systems that enable students to achieve their learning goals satisfactorily. Learning methods that are interesting and actively involve students tend to be more effective. type cooperative learning requires each student to contribute to their group. Apart from that, group members can support and motivate each other and improve each student's understanding. The research method used is a quantitative quasi-experiment (Quasi Experiment) with a research design. Sampling was carried out using the Purposive Sampling technique. Each sample in the experimental class and control class consisted of 32 students. This research data was obtained from the results of the posttest and pretest which used multiple-choice questions totaling 20 questions. Data collection was carried out using observation and documentation techniques. Data analysis techniques include validity testing to determine whether the research instruments used are reliable and hypothesis testing to determine if there is a significant influence on the sample. The average result for the Experiment class was 94.53 while the control class was 52.19. Based on research, the results showed that the use of the learning model in experimental classes was more effective in improving student learning outcomes compared to classes that used conventional approaches in PAI and Character subjects in class VII. So it can be concluded that there is an influence of the use of the learning model on student learning outcomes in Islamic Education and Character subjects in Class VII at SMPN 1 Sumberrejo